African Influences in Atlantic World Culture: Julie Dash's Daughters of the Dust. Issue 5 (May 2016) - M'Baye, Babacar
Abstract: This essay has a double aim. First, it will discuss key insights from past and recent scholarship on African influences in Atlantic world cultures. The overview will show the contributions of key, yet largely unknown, scholarship on African retentions in the Atlantic world that deserves more attention for its implications for literary genealogies. Using Julie Dash's 1997 novel Daughters of the Dust, which was adapted from a 1991 film of the same title, as an example, the second part of this essay will examine the ways in which the literary narrative recreates historical and cultural tropes of traditional African societies as they are refigured in the Black Atlantic world, under the conditions of African‐Americans during slavery. Dash's book helps us trace Africanisms in the Gullah culture of Coastal South Carolina to their origins in African traditions, following these threads as they are woven into African‐American migrations to Harlem and homecomings to the South, as well as celebrations of African aesthetics and preservation of a circum‐Atlantic memory. By placing Daughters of the Dust in its proper historical contexts, we see that the forced alienation of Africans in the Americas did not prevent the strong survival and reinvention of African cultures and aesthetics in the United States.